Methodological Aspects of Forming Integrated Skills in Students During the Teaching of Special Subjects - Sagatov Ibrohim Raufovich (Scientific Trends, 2025)
This article discusses methodological approaches, practical methods and ways to increase their effectiveness in the process of teaching special subjects. Integrated skills are the combined acquisition of theoretical knowledge and practical skills, which are important in preparing competitive specialists in the labor market.
Keywords: Professional education, special subjects, didactic principles of teaching, subject - education, personnel training, youth, teaching methodology of special subjects, tasks of special subjects, transformation, e-learning methodological complex.